Cost-effectiveness of treatment of acute otorrhea in children with tympanostomy tubes - van Dongen, Thijs M A; Schilder, Anne G M; Venekamp, Roderick P; de Wit, G Ardine; van der Heijden, Geert J M G (Pediatrics (Evanston), 2015)
Acute otorrhea is a common problem in children with tympanostomy tubes. We recently demonstrated that treatment with antibiotic-glucocorticoid eardrops is clinically superior to oral antibiotics and initial observation. The aim of this study was to assess the cost-effectiveness of these three common treatment strategies for this condition. We performed an open-label pragmatic trial in which 230 children with acute uncomplicated tympanostomy-tube otorrhea were randomly allocated to receive 1 of 3 treatments: hydrocortisone-bacitracin-colistin eardrops, oral amoxicillin-clavulanate suspension, and initial observation (no assigned medication prescription to fill). Parents kept a daily diary capturing ear-related symptoms, health care resource use, and non-health care costs for 6 months. At 2 weeks and 6 months, the study doctor visited the children at home performing otoscopy. Using a societal perspective, treatment failure (otoscopic presence of otorrhea at 2 weeks) and number of days with otorrhea as reported in the daily diary were balanced against the costs. Antibiotic-glucocorticoid eardrops were clinically superior to oral antibiotics and initial observation both at 2 weeks and 6 months. At 2 weeks, mean total cost per patient was US$42.43 for antibiotic-glucocorticoid eardrops, US$70.60 for oral antibiotics, and US$82.03 for initial observation. At 6 months, mean total cost per patient was US$368.20, US$420.73, and US$640.44, respectively. Because of the dominance of eardrops, calculating incremental cost-effectiveness ratios was redundant. Antibiotic-glucocorticoid eardrops are clinically superior and cost less than oral antibiotics and initial observation in children with tympanostomy tubes who develop otorrhea.